Research and application of Internet of things in power transmission and distribution system - Jianming LIU; Ziyan ZHAO; Xiang JI (物联网学报, 2018)
Power industry is the important energy industry which relates to national economy and the people’s livelihood,and it has a significant meaning to ensure safe and stable operation of power transmission and distribution system.Combined with monitor and operation requirement of power transmission and distribution system,application system for monitoring,inspection,security and interactive service of layered power transmission and distribution system was built based on Internet of things technology.Meanwhile,framework and solutions for security system of electricity Internet of things was established,and demonstration project for system verification was established.